2015
DOI: 10.1016/j.ehb.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Auspicious birth dates among Chinese in California

Abstract: The number eight is considered lucky in Chinese culture, e.g. the Beijing Olympics began at 8:08 pm on 8/8/2008. Given the potential for discretion in selecting particular dates of labor induction or scheduled Cesarean section (C-section), we consider whether Chinese-American births in California occur disproportionately on the 8th, 18th, or 28th day of the month. We find 2.3% "too many" Chinese births on these auspicious birth dates, whereas Whites show no corresponding increase. The increase in Chinese birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…To our knowledge, this cultural preference is not found in most western populations, although superstitious belief in auspicious dates and times of delivery is quite common in Thai society, as well as Chinese families. A previous study conducted in California found a large number of Chinese births on the auspicious dates of the; 8th, 18th, and 28th day of the month, but no corresponding increase among the Whites [22]. Some people have a strong belief in destiny; wherein, they believe that birth time determines the course of their life.…”
Section: Resultsmentioning
confidence: 92%
“…To our knowledge, this cultural preference is not found in most western populations, although superstitious belief in auspicious dates and times of delivery is quite common in Thai society, as well as Chinese families. A previous study conducted in California found a large number of Chinese births on the auspicious dates of the; 8th, 18th, and 28th day of the month, but no corresponding increase among the Whites [22]. Some people have a strong belief in destiny; wherein, they believe that birth time determines the course of their life.…”
Section: Resultsmentioning
confidence: 92%
“…We also examine seasonal and weekly patterns in Dutch marriages. Previous research has considered how births are timed to coincide with or avoid particular dates (Levy, Chung and Slade 2011;Almond, et al 2015) and how birth timing correlates with child and adult outcomes (Buckles and Hungerman 2013); however, to our knowledge, we are the first to study how this type of marriage timing is associated with later outcomes.…”
mentioning
confidence: 89%
“…It showed that there are 6% higher rate of CS on auspicious dates which are 8th, 18 th and 28th of the month especially for male babies and much lesser (5%) on Chinese unlucky dates 4th, 14 th and 24 th . 13 Also studies have been done reporting that birth frequency varies according to seasons. 14 In Australia and United States (US) there are 7.7% lesser births on Friday the 13th and 11% lesser on Halloweens respectively showing effects of these superstitions on western culture too.…”
Section: Auspicious Day and Time Of Birth-cultural Influencesmentioning
confidence: 99%